Microscopic description of odd-odd transitional nuclei by using interacting-boson-fermion -model - M. Ghapanvari; N. Amiri; M.A. Jafarizadeh; H. Hossein Khani (مجله علوم و فنون هسته‌ای, 2020)
Studying the dynamical behavior of various nucleus systems has become an interesting subject of research over recent years in nuclear physics. The Energy spectrum and magnitude of momentum of electric and magnetic multi-poles may describe the behavior of a nuclei collection under a special symmetry group. In this paper, solvable algebraic models by using the aﬃne SU(1,1) Lie Algebra and proton, and neutron degrees of freedom in the framework of an  interacting-boson-fermion-fermion model(IBFFM) is suggested to determine the exact energy and eigenstate of the  transitional odd-odd mass nuclei. The main goal is to study the dynamical behavior of the nucleus in the transition state and then to investigate the special conditions that make this transition process possible. The positive parity low-lying energy states of the 60−66Cu isotopes within the proposed methods are investigated. The obtained results compare well with the available experimental data and IBFFM-1, which augments the reliability of the wave function and Hamiltonian obtained within the suggested IBFFM-2 model. The values of control parameters confirm the mixing of both vibrating and rotating structures in the 60−66Cu isotopes.